Peso-Dollar forward market analysis: Explaining arbitrage opportunities during the financial crisis - Juan R. Hernández (Banco de México, 2014)
Using a vector error correction model I test whether shocks in the funding liquidity conditions in the U.S. and Europe separately explain deviations from the covered interest parity (CIP) between the U.S. Dollar and the Mexican Peso. I find that: (1) Apparent deviations from the CIP seem to be persistent, unless a closer measure to the true costs of funding for the agents is considered. (2) A stable long-run equilibrium relation emerges when I include the effects of funding liquidity shocks stemming from the U.S. and Europe. (3) The exchange rate forward premium adjusts towards a long-run equilibrium relation given by the CIP. (4) Surprisingly, the yield on 1-month Mexican CETEs has its own stochastic trend despite the strong relation between the U.S. and Mexico's economies. (5) Analysis confirms that both future and spot exchange rates are affected by shocks stemming from the U.S. Treasury Bills, the funding liquidity in the U.S. and Europe, and the Mexican CETEs.
Keywords: C58; F31; G12; G13; G14; 330; Covered Interest Parity; Forward and Spot Exchange Rates; Structural Vector Error Correction Model